PENGARUH PROFITABILITAS, TRANSFER PRICING DAN KEPEMILIKAN ASING TERHADAP TAX AVOIDANCE PADA PERUSAHAAN MANUFAKTUR SEKTOR INDUSTRI BARANG KONSUMSI YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) PERIODE 2019–2023 - Walid Hasbi; Achmad Fadjar (LPPM STIE Muhammadiah Bandung, 2025)
This research aims to determine the effect of profitability (ROA), transfer pricing and foreign ownership on tax avoidance in manufacturing companies in the consumer goods industry sector listed on the Indonesia Stock Exchange (IDX) for the 2019-2023 period. The population in this study were all manufacturing companies in the consumer goods industry sector on the Indonesia Stock Exchange totaling 55 companies in the 2019-2023 period. The research method used in this study was purposive sampling, so that the final sample obtained was 8 companies that met the criteria with the help of Eviews 12 2025 Software. The data source in this study is secondary data obtained from financial reports and annual reports on the website www.idx.co.id. Based on the results of the study, Profitability (ROA) has a negative and insignificant effect on tax avoidance, Transfer Pricing has an effect on tax avoidance and Foreign Ownership has an effect on tax avoidance.